2007
DOI: 10.4315/0362-028x-70.10.2259
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Salmonella Contamination of Non–United Kingdom-Produced Raw Shell Eggs on Retail Sale in the Northwest of England and London, 2005 to 2006

Abstract: This survey was prompted by a change in the epidemiology of Salmonella Enteritidis infections in England and Wales and elsewhere in Europe and, to our knowledge, is the first survey to provide information on Salmonella contamination of non-United Kingdom eggs on retail sale. Based on 10,464 non-United Kingdom eggs (1744 pooled samples of six eggs) purchased between March 2005 and July 2006, the total weighted prevalence estimate for all Salmonella detected in non-United Kingdom eggs was 3.3%. Of the eggs sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 12 publications
2
17
0
2
Order By: Relevance
“…The low prevalence may be due to testing being geographically restricted to a single small island. Little et al (2007) found that of 1744 samples of six pooled eggs, Salmonella was found in 157 samples (9%). All 157 isolations were from the shell of the eggs, and of these 157, 10 had also Salmonella in the contents.…”
Section: Discussionmentioning
confidence: 99%
“…The low prevalence may be due to testing being geographically restricted to a single small island. Little et al (2007) found that of 1744 samples of six pooled eggs, Salmonella was found in 157 samples (9%). All 157 isolations were from the shell of the eggs, and of these 157, 10 had also Salmonella in the contents.…”
Section: Discussionmentioning
confidence: 99%
“…Eggshell contamination occurs more frequently than the contamination of the egg contents Davies and Breslin, 2004;Little et al, 2007b;Little et al, 2008). There is a non-linear (quadratic) relationship between infection prevalence in laying hens and the rate of eggshell contamination but a linear relationship between the rate of contamination of egg contents and the prevalence of infected laying hens in a flock, with eggshell contamination occurring at a much higher rate than that of egg contents (Arnold et al, 2014a).…”
Section: Salmonella Prevalence and Serovar Distribution Among Isolatementioning
confidence: 99%
“…Two studies sampled eggs from Salmonella positive flocks (Chemaly et al, 2009;Davies & Breslin, 2004). One study Little, Walsh, et al, 2007) targeted specifically eggs involved in outbreaks of SE in humans. Table 1 summarizes this information for each survey.…”
Section: Surveys On Salmonella Contamination In Table Eggsmentioning
confidence: 99%